Femmes en armes, action collective féminine et projet révolutionnaire : l’émancipation féminine face aux enjeux de la construction nationale au Pérou (19e-20e) - Camille Boutron (Nuevo mundo - Mundos Nuevos, 2014)
Armed violence plays an important role in historic Peruvian national identity. While in the 19th century warfare was associated to the defense of the territory, in the 20th century it was more considered as an instrument of emancipation promoting various political ideologies. In every case, armed violence is interpreted as a patriotic act in a nation that struggles to find its unity. Peruvian history traditionally admits a role of symbolic resistance for women. Nevertheless, it is interesting to note that women’s participation to armed violence is not analyzed in the same way according to the distinctive period when it takes place. While in the 19th century Peruvian women’s presence on battlefields is related through patriotic notions, things changed in the 20th century as the first massive feminist mobilizations began to interfere with revolutionary projects.